Trends and Insights in Free Cash Flow Theory: A Systematic Review of Corporate Dividend Policies (2020-2025) - Wahyuni Maisarah Pane; Sambas Ade Kesuma; Risanty; Firman Syarif; Iskandar Muda (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2025)
This systematic literature review examines research trends on Free Cash Flow (FCF) Theory between 2020 and 2025, focusing on its influence on corporate financial decisions, particularly dividend policy. Seventeen peer-reviewed articles were analyzed to identify patterns, key findings, and theoretical insights regarding FCF application across diverse organizational contexts. The review reveals that firms with higher free cash flow generally exhibit greater flexibility in dividend distribution, although factors such as ownership structure, market conditions, and external events, including the COVID-19 pandemic, can moderate this relationship. FCF also plays a crucial role in enhancing investment efficiency, managing agency conflicts, and signaling financial health to stakeholders. While the application of FCF Theory offers benefits such as improved shareholder value and stronger governance, it faces obstacles from firm-specific characteristics, regulatory differences, and market fluctuations, as well as challenges in accurately measuring free cash flow and interpreting its implications for corporate policies. Overall, FCF Theory remains a pivotal framework for understanding corporate financial behavior, emphasizing the need for contextual and empirical considerations in its application. Keywords: Free Cash Flow Theory; Dividend Policy; Corporate Financial Decisions; Agency Conflict; Corporate Governance; Investment Efficiency.